Excess Cancer Risk Assessment from Some Common X-Ray Examinations in Sabzevar County - Mohammad Taghi Bahreyni Toossi; Hassan Zarghani (Iranian Journal of Medical Physics, 2011)
Introduction: Nowadays ionizing radiation has a considerable contribution in medical diagnostic and treatment. Using ionizing radiation is increasing rapidly, so biological effects of ionizing radiation should be considered more. X-rays in the range of diagnostic radiology have hazardous effects and risks that are defined as random effects. These effects obey the LNT hypothesis that occur at low doses and include many types of cancer and genetic mutations. So it is very important to assess the risk of exposure in medical examinations. Cancer is one of these hazardous risks caused by low dose ionizing radiation that may occur during life after exposure. According to BEAR 7, low dose radiation is defined as radiation that produces doses near zero up to 100 mSv. Materials and Methods: This work was carried out in eight radiology centers in the Sabzevar county of Iran for 485 patients in eight typical x-ray examinations chosen for the study: chest PA, chest AP, lumbar spine AP, lumbar spine LAT, pelvis AP, abdomen AP, skull AP and Lat. In order to estimate the excess cancer risk, we need to obtain collective effective dose caused by radiation in the study population. Usually effective dose offers precise assessment of radiography examination injuries in adult patients. In this study, we used the PCXMC Monte Carlo based software to obtain effective dose and organ dose. This software calculates organ and effective dose following input of patient and radiographic conditions. Results: Average patient weight and height, entrance surface dose, parameters used for each type of examination, and DAP values were entered. Effective dose, collective effective dose, number of radiographs per year and the excess cancer risk arising from these radiographic examinations were then calculated.  Discussion and Conclusion: Excess risk of fatal cancer due to x-ray examinations in the study population was calculated by collective effective dose. This risk in the population is about 0.42 cases suffering fatal cancer per year in this county. If the doses from other diagnostic radiology procedures, in which absorbed dose to patients are considerably higher than conventional radiography, are added to this amount, then the excess risk will be significantly greater than that obtained in this assessment.